Intralesional bleomycin and sodium tetradecyl sulphate for haemangiomas and lymphangiomas - Man Mohan Harjai; Manvendu Jha (Wolters Kluwer Medknow Publications, 2012)
Background: To compare the efficacy of intralesional bleomycin and sodium tetradecyl sulphate in treatment of haemangiomas and lymphangiomas. Patients and Methods: Between July 2007 and May 2009, 120 patients, sixty each of peripheral haemangiomas and lymphangiomas, were administered intralesional injection of bleomycin in a dose of 0.5-1 U/kg in children less than one year of age and 1 to 15 units in children more than one year of age and 1 to 3 ml of 2% sodium tetradecyl sulphate, depending on the size of the lesion at intervals of 14 days. Patients more than 20 years of age and those with diffuse or visceral lesions were excluded from the study. Results: Complete resolution occurred in 16 patients (53%) of haemangiomas and 14 patients (47%) of lymphangiomas treated with bleomycin, while the results were 12 patients (40%) and 10 patients (33%), respectively, in sodium tetradecyl sulphate group. The satisfactory resolution (resolution more than 50%) occurred in eight patients (27%) of haemangiomas and lymphangiomas groups treated with bleomycin, while the results were six patients (20%) and eight patients (27%), respectively, in sodium tetradecyl sulphate group. Poor response rate was observed in six patients (20%) of haemangiomas and eight patients (27%) of lymphangiomas of bleomycin group and 12 patients (40%) of haemangiomas and lymphangiomas in sodium tetradecyl sulphate group. No pulmonary fibrosis or other serious side effects were found. Conclusions: Intralesional bleomycin and sodium tetradecyl sulphate are effective sclerosants in peripheral haemangiomas and lymphangiomas, but bleomycin was found to be more efficacious.